Short Messaging System Based Security Box using Arduino and GSM Module - Safial Islam Ayon (Journal of Telematics and Informatics, 2018)
Nowadays security is a vital issue in our day to day life. In the current world, crime becomes increasing and people want to secure their asset at their house. In this situation, an owner wants an advance technology so that he doesn’t worry about the assets when he doesn’t present in his house. Using wireless technologies and a good user-friendly interface make the home safety system more attractive. This paper deliberates a simple but very effective technique which will be applied to home security. SMS (Short Messaging System) based security box reduce the rate of the crime and secure our assets. The box is designed in such a way that when someone except the owner opens the box it will send an SMS to the owner mobile using the GSM (Global System for Mobile Communication) module. Main motive about this paper is to make a low-cost security box but its benefit will be high.